Sexual Exploitation of Children in the Digital Age in the Victimology Perspective - Marisa Kurnianingsih; Khudzaifah Dimyati; Kelik Wardiono; Absori Absori (Jurnal Jurisprudence, 2021)
Purpose: This study aims to determine the criminal law policy on sexual exploitation in Indonesia and discover the current legal policy from the perspective of victimology.Methodology: This study is based on doctrinal legal research or normative juridical procedures with a legal perspective in the traditional sense of “law in the book”. Normative legal research is essentially a legal research library in which the author studies the legal principles beginning with specific sectors of the legal system and the identification of legislatively enacted legal norms.Results: The findings revealed that the criminal law policy on sexual exploitation in Indonesia and the current legal policy from a victimology view, comprising the legal protection from Law Number 21 of 2007 concerning the Crime of Trafficking in Persons, Law Number 23 of 2002 concerning Protection Children, and Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, have attempted to fulfill the rights of victims, although a detailed explanation of legal protection efforts has been more based on the child protection law. Moreover, according to victimology, focusing on victims, criminal law policies addressing incidents of human trafficking or, more specifically, commercial sexual exploitation of children have prioritized victims’ interests.Benefits: This study was designed to serve as a reference for the government and parties concerned with Indonesia’s criminal law policy on sexual exploitation and its current legal policy from a victimology viewpoint. It is intended to result in law enforcement being more equitable and capable of combating sexual exploitation in the digital age.Novelty/Originality: Regarding responsibility for certain sorts of child sexual exploitation, the child protection legislation is more onerous than the trafficking statute in terms of penalties and threats. The two laws have endeavored to uphold victims’ rights in legal protection. However, the child protection statute includes a more extensive description of the legal protection measures. According to victimology, focusing on victims, criminal law policies addressing incidents of human trafficking or, more specifically, commercial sexual exploitation of children have emphasized victims’ interests